City as a system: A systems approach to urban planning and development - Parysek, Jerzy; Mierzejewska, Lidia (Bulletin of Geography. Socio-economic Series, 2025)
The article presents the evolution of a systems approach in socio-economic geography and spatial management from its first application in Polish geography to the times of its gradual use within Complexity Theory. This evolution is accompanied by the transition from the systemic attitude in a cognitive process (geography) to its practical use (spatial management). However, particular emphasis was put on the reconstruction and development of a highly complex functional system which is the city and the use of a systems approach in planning its development. After the general overview of the system as it is understood, the article shows interactional living environment models and a territorial social system. Then, it demonstrates the use of systemic views in relation to the city in the form of urban ecosystem conceptions, a sustainable city model, and also an organicist city model, including the life of the city as an organicist model of its functioning, and city resilience. The final part deals with the perspectives and determinants brought by Complexity Theory in the realm of cognition and practice. What was also evaluated was the possibility of the application of the systems approach (ideas, conceptions, models) with respect to cognition and practice (urban development and planning) in the current state of science and spatial management in Poland.